PENGARUH PENGHILANG TANIN DARI JENIS PALA TERHADAP SARI BUAH PALA - Sintha Suhirman; Hadad EA; Lince Lince (Buletin Penelitian Tanaman Rempah dan Obat, 2006)
The effect of tannin remover from the kinds of nutmeg on nutmeg juiceHaving special flavor, the flesh of nutmeg is potensial tobe processed into juice product.  However, harsh flavor and bitter aftertaste in this fruit influences the taste of nutmeg juice.  Nutmeg juice would be better if composition of acid, sugar, vitamine, and other phenolic materials could be arranged.  Nutmeg juice contained flavor and its fruit characteristic colour with pH 4.00 – 4.50 (materials of acid food).  The objective of the research was to improve the taste of nutmeg juice by reducing harsh flavor using tannin removing agents, formulation improve-ment and selection of nutmeg kinds. The   experi-ment was arranged in a completely randomized design with aplications. Research were  conduc-ted in six stages. The first step, determination of treatment of harsh reduction. The second step, ratio determination between nutmeg flesh, water and  percentage of sugar. The third step, duration of blanching process. The fourth step, optimation based on combination of the result of the first and third stages. The fifth step, determination of nutmeg species to be processed into nutmeg juice. The sixth step, organoleptic test by 30 panelist The result showed that the usage of albumin  1% in nutmeg juice was more preferred and  could reduce harsh flavor  and declined content of 3 544.06 mg per 100 g material, while CaCl3 solution 2.00% for 12 hours could reduce tannn to be 4 271.22 mg per 100 g material.  The result of organoleptic test showed that the taste of nutmeg juice could be enhanced using best formulation in every stage i.e. albumin 1.00%. Without blanching, ratio nutmeg flesh and water 1 : 4, 25% sugar, the use of Patani nutmeg, Banda nutmeg and Irian nutmeg in fact preferred by panelist.